Study on Initial Disturbance of Airborne Missile’s Horizontal Backward Derailment under Continuous Gust - Xiao Pan; Yi Jiang; Xinlin Wei; Mingjun Li (International Journal of Aerospace Engineering)
This paper studies the effect of continuous gusts on the initial disturbance of the airborne missile’s horizontal backward derailment on large transport aircraft. The longitudinal fluctuation of the airborne launching platform under continuous gust was obtained with different calculation methods, and the finite element model of the derailing process was established then verified by experiments. Finally, combined with the longitudinal fluctuation of the launching platform and the finite element model of the missile and launching platform, the influence of platform fluctuation on separation time, missile speed, pitch angle, and descending distance while derailing was studied and analyzed. It is found that the longitudinal fluctuation of the launching platform is similar to that of the gust but lags behind, and the missiles under the fluctuating platform have longer separation time, lower derailing speed, and greater derailing pitch angle and descending distance.